Chronic hepatitis C in hemodialysis patients: Prevalence and liver fibrosis impact in the National Center for Renal Health in Peru - Padilla-Machaca, P. Martin (2022)
Background: Hepatitis C (HCV) remains a serious public health problem in high-risk persons such as patients on chronic hemodialysis. We aimed to estimate the serological prevalence of HCV, the HCV viral load and genotype, and liver fibrosis stage among patients on chronic hemodialysis at the National Renal Health Center in Lima, Peru. Methods: From June 2019 to March 2021, all patients who received chronic hemodialysis were invited to participate. Subjects who provided written informed consent were enrolled. Patients with HCV-positive serology underwent determination of HCV viral load. Samples from subjects with detectable viral load, underwent determination of HCV genotype. Then, HCV infected subjects underwent determination of liver fibrosis using transitional elastography (Fibroscan 402): Metavir score: F0–F1: 2.5–7.5 kPa, F2: 7.6–9.5 Kpa, F3: 9.6–12 Kpa, F4 (Cirrhosis): 12.1–75 Kpa. Results: Of the 303 subjects invited to participate, 174 (57.4%) subjects gave their written consent. Mean age was 52 years (range 22–91) and 116 (66.6%) were male. HCV serology was positive in 35.1% of patients (61/174); however, the prevalence of positive serology with detectable viral load was 20.11% (35/174). Genotype 1a was the most prevalent (85%). The majority (83.6%) of subjects with detectable viral load had values lower than 800.000 IU/mL. Twenty-nine of those 35 subjects underwent elastography evaluation, and 13 (44.8%) of them were found to have stage F2–F4 fibrosis. Conclusions: The prevalence of HCV at the largest reference center for hemodialysis in Lima remains high, with GT1a predominance, viral load usually below 800,000 IU/mL and significant liver fibrosis.